2019
DOI: 10.3899/jrheum.180868
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Axial Spondyloarthritis on Mental Health: Results from the Atlas

Abstract: Objective.To assess the risk of mental disorders in patients with axial spondyloarthritis (axSpA) and to examine the factors associated with this.Methods.In 2016, a sample of 680 patients with axSpA were interviewed as part of the development process for the Atlas of Axial Spondyloarthritis in Spain. The risk of mental disorders in these patients was assessed using the 12-item General Health Questionnaire scale. Additionally, the variables associated with the risk of mental disorders were investigated, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
2
14
3
2
Order By: Relevance
“…Psychological distress has been demonstrated to lead to poorer disease outcomes by enhancing symptom burden, decreasing adherence to Bold values denote statistical significance at the p < 0.05 level treatment and increasing disability [27]. Additionally, in patients with axSpA, the risk of mood disorders is explained mainly by the degree of disease activity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress has been demonstrated to lead to poorer disease outcomes by enhancing symptom burden, decreasing adherence to Bold values denote statistical significance at the p < 0.05 level treatment and increasing disability [27]. Additionally, in patients with axSpA, the risk of mood disorders is explained mainly by the degree of disease activity [28].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al ,27 in a meta-analysis of 16 studies, estimated the prevalence of at least moderate depression in patients with axSpA as 15%, based on a HADS score of ≥11. Garrido-Cumbrera et al ,28 in a sample of 680 patients as part of the Atlas of Axial Spondyloarthritis in Spain, reported that high disease activity was a risk factor for poor mental health, but the current study emphasises that poor mental health independently predicts worse QoL. A meta-analysis of the co-occurrence of fibromyalgia in axSpA estimated a prevalence of 13%,29 compared with a prevalence in the general population of around 2%–5%,30 and we have previously shown within BSRBR-AS that patients who have comorbid fibromyalgia have the same absolute improvement in QoL when treated with anti-TNFα therapy, but their QoL prior to and on treatment remains worse.…”
Section: Discussionmentioning
confidence: 99%
“…The methodology of the EMAS study is described in detail elsewhere. 2 For the purpose of this analysis on mental health, data from Spain were excluded as they have been previously published, 9 therefore our final sample size presented here is 2,166.…”
Section: Methodsmentioning
confidence: 99%
“…To determine mental disorder risk among patients with axSpA, the Likert scale was transformed to 0, 0, 1, 1, and the threshold for mental disorder risk set at ≥3 as supported by literature. 9 The GHQ-12 is a screening measure for identifying minor psychiatric disorders in the general population, used to encompass common symptoms of anxiety social dysfunction and loss of confidence. 12 It is not a diagnostic instrument.…”
Section: Patient-reported Outcome Measuresmentioning
confidence: 99%